EVALUATION OF PLATELET PARAMETERS IN CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS- A TERTIARY CARE CENTRE EXPERIENCE - Dr. Azka Qazi; Dr. Sabina Khan; Dr. Shivali Sehgal; Dr. Nehal Ahmad; Dr. Anwar Habib (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Chronic Kidney Disease (CKD) is a global issue, with cardiovascular complications as a common cause of mortality in CKD patients on hemodialysis (HD). Platelet indices play major mechanism in pathological processes of vascular thrombosis.Aim: The aim of the study was to assess platelet parameters including count and platelet indices namely Mean platelet volume (MPV), Platelet large cell ratio (P-LCR), Platelet distribution width (PDW) and Plateletcrit (PCT) in CKD patients undergoing hemodialysis.Methods: A retrospective evaluation was conducted on the biochemical and hematological parameters accessed from the hospital records of hemodialysis patients who have chronic kidney disease for a period of one year. Platelet indices were obtained using Sysmex-XN 1000 automated six part hematology analyzer. Statistical Analysis: The data was entered into Excel spreadsheet (Microsoft, Redmond, Washington) version SPSS 20.0 for data analysis. Results: The results showed male predominance (73.33%) with 45 to 65 years age group commonly affected by CKD. The Mean platelet volume, Platelet distribution width and Plateletcrit were found to be elevated in CKD patients in comparison to controls. However only Mean platelet volume and Platelet distribution width were found statistically significant and Platelet counts were lower among the study population.Conclusion: Early screening of alterations in platelet parameters may prove to be an efficient factor in risk stratification of CKD patients prone to develop venous thromboembolism and cardiovascular diseases.